2014
DOI: 10.1364/ao.53.001449
|View full text |Cite
|
Sign up to set email alerts
|

Design study of nanograting-based surface plasmon resonance biosensor in the near-infrared wavelength

Abstract: A key issue with surface plasmon resonance (SPR) biosensors, which are the focus of many researchers, is improving their sensitivity to detect lower amounts of analyte in a solution. Most SPR developments have focused on the grating-based sensitivity-enhancement approach. In addition to sensitivity, a substantial enhancement of other sensor characteristics such as resolution and signal-to-noise ratio (SNR) is desired for designing a practical sensor. So, in this paper, the characteristics of surface plasmon po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…It has been demonstrated in our previous work that a laser wavelength of 984 nm allows the biosensor with parameters of P and f.f equal 50 nm and 0.5, respectively, operates near the band edge wavelength related to the highest dg of 40 nm which is located in flattened part of dispersion map [12]. As described the sensor at this band edge wavelength shows the highest sensitivity.…”
Section: Numerical Modelmentioning
confidence: 65%
See 4 more Smart Citations
“…It has been demonstrated in our previous work that a laser wavelength of 984 nm allows the biosensor with parameters of P and f.f equal 50 nm and 0.5, respectively, operates near the band edge wavelength related to the highest dg of 40 nm which is located in flattened part of dispersion map [12]. As described the sensor at this band edge wavelength shows the highest sensitivity.…”
Section: Numerical Modelmentioning
confidence: 65%
“…From our previous study using an angle interrogation type of SPR biosensor such as proposed sensor in this letter, dispersion curve study revealed that high sensitivities can be obtained in the sensor working in operating wavelength near the band edge wavelength which is located in the flattened part of the dispersion curve [12]. It has been described that operating near the bandgap is more sensitive [21].…”
Section: Evaluation Of Grating Height (Dg) Metal Film Layer Thicknesmentioning
confidence: 75%
See 3 more Smart Citations